URGENSI ZONA BEBAS PEKERJA ANAK DI KABUPATEN KUTAI KERTANEGARA - La Sina (Masalah-Masalah Hukum, 2014)
Child protection is an effort to provide protection to children that their rights are not discriminated against and in order to grow, thrive and excel, optimally in accordance with human dignity. Child labor free zones is a program that was first performed by Kertanegara Kutai district to raise the dignity of the child. Urgency of child labor free zones is to provide protection of children as the mandate of Law No. 23 of 2002 on the Protection of Children. The first step should be able to also followed by District / City in Indonesia.